A Pilot Double-Blind Placebo-Controlled Randomized Clinical Trial to Investigate the Effects of Early Enteral Nutrients in Sepsis - Faraaz Ali Shah, MD, MPH (Wolters Kluwer, 2021)
OBJECTIVES:. Preclinical studies from our laboratory demonstrated therapeutic effects of enteral dextrose administration in the acute phase of sepsis, mediated by the intestine-derived incretin hormone glucose-dependent insulinotropic peptide. The current study investigated the effects of an early enteral dextrose infusion on systemic inflammation and glucose metabolism in critically ill septic patients. DESIGN:. Single-center, double-blind, placebo-controlled randomized pilot clinical trial (NCT03454087). SETTING:. Tertiary-care medical center in Pittsburgh, PA. PATIENTS:. Critically ill adult patients within 48 hours of sepsis diagnosis and with established enteral access. INTERVENTIONS:. Participants were randomized 1:1 to receive a continuous water (placebo) or enteral dextrose infusion (50% dextrose; 0.5 g/mL) at 10 mL per hour for 24 hours. MEASUREMENTS AND MAIN RESULTS:. We randomized 58 participants between June 2018 and January 2020 (placebo: n = 29, dextrose: n = 29). Protocol adherence was high with similar duration of study infusion in the placebo (median duration, 24 hr [interquartile range, 20.9–24 hr]) and dextrose (23.9 hr [23–24 hr]) groups (p = 0.59). The primary outcome of circulating interleukin-6 at end-infusion did not differ between the dextrose (median, 32 pg/mL [19–79 pg/mL]) and placebo groups (24 pg/mL [9–59 pg/mL]; p = 0.13) with similar results in other measures of the systemic host immune response. Enteral dextrose increased circulating glucose-dependent insulinotropic peptide (76% increase; 95% CI [35–119]; p < 0.01) and insulin (53% [17–88]; p < 0.01) compared with placebo consistent with preclinical studies, but also increased blood glucose during the 24-hour infusion period (153 mg/dL [119–223] vs 116 mg/dL [91–140]; p < 0.01). Occurrence of emesis, ICU and hospital length of stay, and 30-day mortality did not differ between the placebo and enteral dextrose groups. CONCLUSIONS:. Early infusion of low-level enteral dextrose in critically ill septic patients increased circulating levels of insulin and the incretin hormone glucose-dependent insulinotropic peptide without decreasing systemic inflammation.